PRODUCTION OF RELATIVE CLAUSES BY ENGLISH LEARNERS IN KAMPUNG INGGRIS PARE KEDIRI - Novianto, Wawan; Suhandano, Suhandano (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
This study aims to describe relative clauses produced by English Learners in Kampung Inggris Pare Kediri. The description of relative clauses produced is to know the kind of relative clauses English learners can and cannot produce. Data was obtained from learners’ essay in IELTS simulation test part writing. Result says that English Learners can only produce relative clauses which relativize H as subject with 85.7% of percentage, as object with 8.5%, and as adverb with 5.8% of percentage. RCs whose H position is in possessive, object of preposition, and indirect object do not appear in the data. While for relational relative clause, cleft relative clause is also not produced by learners.  Further, error analysis says that the errors learners produce are divided into six types: 1) error in using relativizer, 2) producing unneeded relative clauses, 3) The absence of relative pronouns, 4) Error in using verb in relative clause, and 5) Error in H-V agreement.53.4%